2018
DOI: 10.17221/701/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmospheric and soil water status on photosynthesis and growth in tomato

Abstract: The responses of tomato seedlings to different vapour pressure deficit (VPD) under low soil moisture were studied. Plants were grown in greenhouses with low and high VPD, under both well-watered and water stress conditions. Low VPD was effectively maintained below 1.5 kPa with a micro-fog system. Under well-watered conditions, low VPD resulted in reduced transpiration, but this did not affect plant water status or growth. Water stress induced leaf dehydration and inhibition of growth, but the adverse effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
(14 reference statements)
3
4
0
1
Order By: Relevance
“…Our research has shown that controlling VPD can benefit protected cultivation systems 20,25–27 , similar to other findings 28,29 . However, most such studies focus on VPD levels below 4 kPa and few consider VPD up to or even beyond 5–6 kPa 30 , yet this represents the climate characteristics of most arid and semi-arid areas, such as northwest China.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our research has shown that controlling VPD can benefit protected cultivation systems 20,25–27 , similar to other findings 28,29 . However, most such studies focus on VPD levels below 4 kPa and few consider VPD up to or even beyond 5–6 kPa 30 , yet this represents the climate characteristics of most arid and semi-arid areas, such as northwest China.…”
Section: Introductionsupporting
confidence: 91%
“…The stomatal responses to VPD are actively driven by the phytohormone abscisic acid (ABA) 18 and regulated by rapid gene expression 19 . Stomatal morphology parameters are also significantly affected by VPD 20 . Active physiological stomatal control in response to [CO 2 ] will eventually initiate ion pumping to alter the turgor pressure of guard cells 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Tables 1 and S1). However, no significant difference was observed in T r between each VPD level under drought-stressed conditions, in line with the findings by Du et al (2018), suggesting that soil water deficits overrode the effects of VPD on T r . Additionally, it should be noted that T r of plants grown under VPD3 was significantly higher than those grown under other VPD levels under both irrigation treatments.…”
Section: Ta B L Esupporting
confidence: 87%
“…Results of the two-way ANOVA on leaf net photosynthetic rate (A n ), stomatal conductance (g s ), transpiration rate (T r ), abscisic acid concentration (ABA), stomatal density (SD), leaf relative water content (RWC), leaf area (LA), special leaf area (SLA), shoot dry matter (DM shoot ), water consumption (WU) and water-use efficiency ( It has also been suggested that the stomatal response to RH was not dominated by RH, but a feedback response to transpiration (Mott & Parkhurst, 1991). Inhibition of T r under soil water deficits or low VPD was well documented in previous studies (Du et al, 2018;Schoppach & Sadok, 2012), which was also confirmed in the present study. Soil water deficits appeared to inhibit leaf transpiration rate (T r ) as seen from the substantial decrease in g s under each VPD level during the whole treatment period (Figure 3b,c; Table 1).…”
Section: Ta B L Ementioning
confidence: 79%
“…Knowing from the specialized literature that the carotenoid pigments play a significant part in photosynthesis [12], I may assume, as in the case of chlorophyll, that certain organic substances from the composition of detergents interfere with the carotenoids' action mechanism. Moreover, the photosynthesis provides carbohydrate for plant growth [13].…”
Section: Weight Ratio Of Chlorophylls and Total Carotenoids Analysismentioning
confidence: 99%